Pengaruh Keamanan dan Keselamatan Wisatawan Terhadap Citra Daya Tarik Wisata Kawasan Luar Pura Luhur Uluwatu Kabupaten Badung, Bali - Apul, Valentino Ray Febriano; Anom, I Putu; Suryasih, Ida Ayu (JURNAL DESTINASI PARIWISATA; Vol 11 No 2 (2023): VOL 11, NO 2 (2023): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATA, 2023)
This research was conducted to determine what efforts were made by the managers of the outer area of Pura Luhur Uluwatu in anticipating and handling problems related to the security and safety of tourists and to analyze how much influence the security and safety of tourists have on the image of the Outer Area of Pura Luhur Uluwatu Tourism Attraction. The Outer Area of Pura Luhur Uluwatu is one of the Tourist Attractions on the Island of Bali which is also the habitat of hundreds of wild monkeys around the outer area of the temple which are aggressive and often take valuables belonging to tourists. This noble temple is also a place of morning worship for Hindus. This study uses qualitative and quantitative descriptive methods. The sampling technique is the accidental sampling method by preparing a questionnaire distributed to 100 respondents and calculated with a limit using a Likert scale. The data collection techniques used are through observation, interviews, questionnaires and literature studies. The results of this study conclude that the efforts made by the managers have been very good, namely by installing warning signs, vaccinating the monkeys, preparing handlers who are on guard around the outer area of the temple and along the road from the entrance, and preparing a first aid clinic. These efforts are made by the management to maintain the security and safety of tourists during their travels. Meanwhile, the influence of Security and Safety on Destination Image is indicated by the magnitude of the Correlation and Determination (R2) value of 0.599 with sufficient criteria. This means that 59.9% of the Destination Image variable is influenced by the Security variable (X1) and the Safety variable (X2). This is also indicated by the value of the hypothesis test results which indicate a simultaneous and partial influence between security and safety on the image of the attraction. Keywords: Security and Safety; Destination Image